Financial decentralization in vocational schools: A BLUD governance study - Yeni Triani; Manap Somantri; Asti Putri Kartiwi (Indonesian Journal of Educational Development (IJED), 2026)
This study examines the implementation of financial governance in vocational secondary schools operating under the Regional Public Service Agency (BLUD) framework as part of Indonesia's educational decentralization reform. The research is grounded in the urgency to strengthen institutional autonomy, financial flexibility, and industry relevance in vocational education amid increasing demands for production-based learning and for the development of factory teaching. The study aims to analyze policy implementation, financial planning, operational management, evaluation mechanisms, and governance follow-up practices within BLUD-based schools. A qualitative descriptive approach was employed using a multi-site case study design involving four vocational schools. The research population comprised BLUD-designated vocational schools in Bengkulu Province, from which four schools were purposively selected based on implementation duration, variation in governance performance, and production unit readiness. Research participants included principals, BLUD financial managers, vocational teachers, and representatives from the education office. Data were collected through semi-structured interviews, non-participant observations, and analysis of institutional documents, using validated interview guides and observation protocols. Data were analyzed using the CIPP evaluation model supported by interactive data analysis techniques. The findings indicate that BLUD governance has been implemented in a structured manner, enabling flexible financial management, strengthening teaching factory operations, and enhancing experiential learning. Evaluation systems and follow-up actions were found to reinforce accountability in governance and institutional learning. The study concludes that BLUD financial autonomy contributes positively to the quality of vocational education when supported by participatory governance, managerial competence, and sustainable evaluation. It is recommended that policymakers strengthen capacity-building programs, participatory financial literacy, and performance-based monitoring systems to optimize outcomes of BLUD implementation.